Senior Policy in Hungary, Poland and Russia - Urbaniak, Boguslawa; Evseeva, Yaroslava; Patyán, László (Wydawnictwo Uniwersytetu Łódzkiego, 2025)
The monograph considers the notion and scope of senior policy vis-à-vis similar policies, such as social policy on ageing, social policy on old age, and social policy on the elderly. Although retirement policy is unrelated to senior policy, it is also covered in the monograph because of its influence on the financial situation and well-being of the elderly and older adults. A brief review of the demographic situation and main population trends in EU-28 countries is followed by a presentation of senior policies in Hungary, Poland and Russia, and the impact of their retirement policies on the economic situation of older people.